Risk Factors for Violent Injuries and Their Severity Among Men in The Gambia. Issue 6 (November 2018) - Bass, Paul; Sanyang, Edrisa; Lin, Mau-Roung
A matched case-control study was conducted to identify risk factors for injury from physical violence and its severity in Gambian men. Study participants were recruited from eight emergency rooms and outpatient departments in two health administrative regions. Cases were male patients aged ⩾15 years who had been violently injured. A control patient for each case, matched for the hospital or health center, date of injury, gender, and age, was selected from those injured due to nonviolence causes. In total, 447 case-control pairs were recruited. Results of the conditional logistic regression analysis showed that case patients who worked as businessmen (odds ratio [OR], 1.93; 95% confidence interval [CI] [1.16, 3.20]), had monthly household income of ⩾US311 (OR, 2.12; 95% CI [1.06, 4.24]), had two or more male siblings (OR, 2.20; 95% CI [1.15, 4.21]), had consumed alcohol in the past week (OR, 3.32; 95% CI [1.25, 8.84]), and had been physically abused (OR, 5.10; 95% CI [2.71, 9.62]) or verbally abused (OR, 1.63; 95% CI [1.04, 2.56]) in the past 12 months were significantly associated with the occurrence of injury from physical violence. Severe injuries during the violence were significantly associated with events that took place in public spaces, with certain injury mechanisms (being stabbed/cut/pierced, struck by an object, assaulted by fist punching/leg kicking/head-butting, and scalded/stoned), having injuries to the upper extremities, and smoked cigarettes in the past week. Specific public health programs aimed at preventing physical violence and severe injuries against men should be developed in The Gambia based on modifications of the identified risk factors.